PENGGUNAAN METODE YANBU’A SEBAGAI PENDEKATAN BELAJAR BACA TULIS AL-QUR’AN - Riris Setyawati; Eni Fariyatul Fahyuni (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
In a country with a majority Muslim population such as Indonesia, there are still many children, adolescents, to adults whose ability to read the Qur’an is still low. The use of the method is predicted to be one that has a considerable influence on the success of children in learning the Qur’an. The Yanbu’a method is the right choice to be used as an approach to learning to read and write Qur’an. Where this method is indeed prepared for anyone who wants to learn to read and write the Qur’an. This article discusses the Use of the Yanbu’a Method as an Approach to Learning to Read and Write the Qur’an. This study aims to find out how the implementation of the Yanbu’a method in learning to read and write the Qur’an. The type of method used is qualitative descriptive. Data collection techniques using observation, intervies, and documentation. The validity test of data through triangulation and research subjects was carried out in one of the Qur’an Education Parks located in Cangkringmalang Beji Pasuruan Village. The result showed that: First, learning with the Yanbu’a method was carried out two times in one day, namely afternoon and evening. Second, the response of students related to learning with the Yanbu’a method is very varied. Third, there are supporting and inhibiting factors in the implementation of Qur’anic literacy learning.